Implementasi Undang-Undang Pelindungan Data Pribadi: Peran Manajemen Risiko Hukum bagi Prosesor Data Pribadi - Tiara Shafa Putri; Moody Rizqy Syailendra Putra (CV Rewang Rencang, 2024)
With the enactment of Law Number 27 of 2022 concerning Personal Data Protection (Law No. 27/2022), the regulations governing personal data protection have expanded and developed significantly. The implementation of the Law No. 27/2022 provides legal certainty regarding failures in personal data protection in Indonesia. This research employs a normative legal methodology, analyzing legal materials such as the Law No. 27/2022 to address the issues discussed. It also references other materials, including books, journals, and articles related to personal data protection. The purpose of this study is to understand the challenges in implementing the Law No. 27/2022 and the role of risk management during the implementation process. One of the challenges in implementing the Law No. 27/2022 is the absence of several elements mentioned in the law to date, such as implementing regulations that serve as derivative rules and the establishment of a personal data protection authority. Legal risk management plays a crucial role in assisting personal data processors in identifying, managing, and mitigating legal risks associated with data breaches, regulatory non-compliance, and potential legal claims from data subjects.